2022
DOI: 10.3389/fmicb.2022.915773
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptomic and lipidomic analyses indicate that cold stress enhanced the production of the long C18–C22 polyunsaturated fatty acids in Aurantiochytrium sp.

Abstract: Aurantiochytrium sp. belonging to Thraustochytrids are known for their capacity to produce long-chain polyunsaturated fatty acids (PUFAs). However, effects of cold stress accompanied with staged-temperature control on the fatty acid metabolism in Aurantiochytrium sp. were rarely studied. In this study, cold stress (15°C, 5°C) was applied for Aurantiochytrium sp., with the physiological responses (morphology, growth, fatty acid profiling) and gene expression related FA synthesis, lipid metabolism, and regulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…However, Aurantiochytrium sp. cultivated in cold stress (5 o C) for TAG accumulation was found to have 1.2 and 12-fold upregulation of GPAT and LPAT respectively [ 96 ]. Three isoforms of DGAT were found for SR21 i.e., schi_1281 , schi_0446 and schi_1268 .…”
Section: Resultsmentioning
confidence: 99%
“…However, Aurantiochytrium sp. cultivated in cold stress (5 o C) for TAG accumulation was found to have 1.2 and 12-fold upregulation of GPAT and LPAT respectively [ 96 ]. Three isoforms of DGAT were found for SR21 i.e., schi_1281 , schi_0446 and schi_1268 .…”
Section: Resultsmentioning
confidence: 99%
“…There are two distinct pathways for TAG biosynthesis in nature, and almost all the genes involved in these pathways had been predicted in thraustochytrids [ 22 , 23 ]. In our recent study, we found four DGATs, which are the key and rate-limiting enzymes in Kennedy pathway, in thraustochytrid Aurantiochytrium sp.…”
Section: Discussionmentioning
confidence: 99%
“…At the cell growth phase, most of the synthesized PUFAs preferentially incorporated into PL [ 3 , 16 ], and the excess PLs may migrate into TAG catalyzed by Au PDAT. In thraustochytrids, low temperature enhanced the DHA accumulation [ 23 , 25 ], which could remodel membranes to response to cold stress by improving the fluidity and integrity of the membrane. Our previous study found the expression of Au PDAT was depressed at this condition [ 26 ], which may result in the PL accumulation.…”
Section: Discussionmentioning
confidence: 99%
“… To elucidate PBPs biosynthesis's potential association in the cell To provide a direction for subsequent fermentation optimization to improve PBPs yield Saini et al ( 2021 ) P. thermoglucosidasius To resolve a previously unclear bottleneck in anaerobic fermentation To identifying the minimal required supplemented nutrients needed to sustain anaerobic growth Mol et al ( 2021 ) Comparative transcriptomics and lipidomics Aurantiochytrium sp. To elucidate the effects of different temperatures (5 °C, 15 °C) treatments on the biosynthesis of long-chain polyunsaturated fatty acids The accumulation of DHA was increased under 5 °C, the yield of eicosadienoic acid (20:2) increased at 15 °C Song et al ( 2022 ) Genomics, comparative transcriptomics and proteomics Rhodosporidium toruloides To elucidate the molecular mechanism of nitrogen-limited starvation on the accumulation of oil which was helpful for the design of medium and process control during nitrogen-limited fermentation Zhu et al ( 2012 ) Transcriptomics, proteomics, metabolomics Rhodosporidium toruloides To elucidate the molecular mechanism of phosphate-limited starvation on the accumulation of lipids To provide new substances for nutritionally limited production Wang et al ( 2018 ) Proteomics, metabolomics Phaffia rhodozyma It found that succinate increased carotenoid production mainly due to increased acetyl-CoA utilization and cellular respiration rate As a reference for the production of carotenoids from non-fermentative carbon sources Martinez-Moya et al ( 2015 ) Transcriptomics, metabolomics C. zofingiensis To elucidate the molecular mechanism of 0.2 M NaCl maximize both TAG and astaxanthin contents It provided an accumulation of biodiesel in algae under salt stress theoretical basis Mao et al ( 2020 ) Methan...…”
Section: Applications Of Omics Technologies In the Process Optimizati...mentioning
confidence: 99%
“…under different temperatures (5 °C, 15 °C). The study found that the accumulation of docosahexaenoic acid (DHA) increased by 1.25-fold due to upregulated expression of genes involved in fatty acid synthase (FAS) and polyketide synthase (PKS) pathways under 5 °C, and the yield of eicosadienoic acid (20:2) increased by twofold due to upregulated FAS and fatty elongase 3 involved in the FAS pathway at 15 °C (Song et al 2022 ). Besides, Zhao et al studied the effects of low (16 °C) and high (32 °C) temperature treatments on the biosynthesis of carotenoids, lipids, and exopolysaccharides (EPSs) in oleaginous red yeast R. glutinis ZHK.…”
Section: Applications Of Omics Technologies In the Process Optimizati...mentioning
confidence: 99%